Real-time detection of microbial contamination. - Hea-Young Kim
We demonstrate the utility of this molecular engineering-based capture and detection technology for use in homeland defense. This capture technology can be placed on a "chip" where each section contains a different ligand. Intrinsic fluorescence is then used to monitor the binding of biomaterial in each section containing a ligand and determines the nature of the biomaterial (e.g., live bacterial cells, dead cells, spores, or tryptophan/tyrosine containing protein molecules).
Keywords: Biomaterial; Detection technology; Fluorescence; Homeland defense; Microbial contamination; Molecular engineering-based capture; Protein molecules; Real-time detection